From FinTech Adoption to Strategic Performance: A Comparative Systematic Review of SMEs in Indonesia and Malaysia - Achref Boubekri; Tasya Aspiranti; Nunung Nurhayati; Ima Amaliah (Journal of Marketing Management and Innovative Business Review, 2026)
The rapid expansion of Financial Technology (FinTech) has transformed financial service delivery and created new opportunities for SMEs, particularly in emerging economies. This study systematically examines and compares the strategic impacts of FinTech adoption on SME performance in Indonesia and Malaysia through a PRISMA guided systematic literature review of peer-reviewed studies, institutional reports, and official publications from 2018 to 2025. The analysis focuses on financial access, operational efficiency, innovation capability, regulatory environment, and institutional trust. The findings show that FinTech adoption enhances access to finance and improves transactional efficiency in both countries; however, the depth and sustainability of these benefits differ across contexts. In Indonesia, FinTech mainly supports financial inclusion and short-term liquidity management, while in Malaysia it is more deeply integrated into organizational and financial systems, contributing to sustained productivity and strategic resilience. These differences are largely driven by variations in regulatory maturity, institutional support, and organizational readiness. The study concludes that FinTech adoption alone does not guarantee improved SME performance, rather its strategic value depends on the alignment between technological adoption, firm-level capabilities, and institutional environments. The findings offer comparative insights for policymakers and practitioners aiming to strengthen FinTech-enabled SME development strategies in emerging economies.